Advancing the implementation and sustainment of medication assisted treatment for opioid use disorders in prisons and jails - Warren J. Ferguson; Joan Johnston; Jennifer G. Clarke; Peter J. Koutoujian; Kathleen Maurer; Colleen Gallagher; Julie White; Dyana Nickl; Faye S. Taxman (BMC, 2019)
Abstract Background Opioid use disorder (OUD) is among the most prevalent medical condition experienced by incarcerated persons, yet medication assisted therapy (MAT) is uncommon. Four jail and prison systems partnered with researchers to document their adoption of MAT for incarcerated individuals with opioid use disorders (OUD) using their established treatment protocols. Employing the EPIS (Exploration, Planning, Implementation, and Sustainment) framework, programs report on systematic efforts to expand screening, treatment and provide linkage to community-based care upon release. Results All four systems were engaged with implementation of MAT at the outset of the study. Thus, findings focus more on uptake and penetration as part of implementation and sustainment of medication treatment. The prevalence of OUD during any given month ranged from 28 to 65% of the population in the participating facilities. All programs developed consistent approaches to screen individuals at intake and provided care coordination with community treatment providers at the time of release. The proportion of individuals with OUD who received MAT ranged considerably from 9 to 61%. Despite efforts at all four sites to increase utilization of MAT, only one site achieved sustained growth in the proportion of individuals treated over the course of the project. Government leadership, dedicated funding and collaboration with community treatment providers were deemed essential to adoption of MAT during implementation phases. Facilitators for MAT included increases in staffing and staff training; group education on medication assisted therapies; use of data to drive change processes; coordination with other elements of the criminal justice system to expand care; and ongoing contact with individuals post-release to encourage continued treatment. Barriers included lack of funding and space and institutional design; challenges in changing the cultural perception of all approved treatments; excluding or discontinuing treatment based on patient factors, movement or transfer of individuals; and inability to sustain care coordination at the time of release. Conclusions Adoption of evidence-based medication assisted therapies for OUD in prisons and jails can be accomplished but requires persistent effort to identify and overcome challenges and dedicated funding to sustain programs.